Peningkatan Kemampuan Berpikir Kritis Pembelajaran Pendidikan Pancasila melalui Model Group Investigation di Kelas IV SDN Menteng Atas 14 - Aulia, Syifa; Nina Nurhasanah; Edwita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to improve students' critical thinking skills in learning Pancasila Education through the application of the Group Investigation learning model in grade IV elementary school. The sample in this research were grade IV students of SDN Menteng Atas 14 as many as 23 students. the type of method used in this research is Classroom Action Research model Kemmis and Mc. Taggart model which consists of four stages, namely, planning, action, observing, and reflecting. The data collection techniques used were observation, interviews, and tests. The results of the research by applying the Group Investigation learning model can improve the critical thinking skills of grade IV students. In cycle I the acquisition of critical thinking skills test scores amounted to 56.5%. Then, in cycle II with the acquisition of critical thinking skills test score of 91%. This shows an increase in critical thinking skills from cycle I to cycle II. Therefore, it can be concluded that learning by using the Group Investiagtion model can improve the critical thinking skills of students in learning Pancasila Education in class IV SDN Menteng Atas 14.